Secondary prevention with antiplatelet medications in patients with antiphospholipid antibody-related stroke - Yang, Wookjin; Chung, Matthew; Ha, Jiyeon; Kang, Dong-Wan; Lee, Eung-Joon; Jeong, Han-Yeong; Kim, Jeong-Min; Jung, Keun-Hwa; Lee, Seung-Hoon (Scientific reports, 2025)
Clinical guidelines recommend warfarin for patients with antiphospholipid syndrome (APS) and ischemic stroke; however, robust evidence is lacking. We investigated the clinical benefits of different categories of antithrombotic medications in ischemic stroke patients positive for antiphospholipid antibodies (aPLs) in real-world practice. We reviewed data from patients with ischemic stroke or transient ischemic attack who tested positive for aPLs. Based on their secondary preventive antithrombotic medications, patients were classified into antiplatelet and anticoagulant categories, and further into warfarin, single antiplatelet therapy (SAPT), dual antiplatelet therapy (DAPT), and direct oral anticoagulant groups. The outcome of interest was a composite of recurrent thrombosis and major bleeding events. Time-varying Cox proportional hazards model was used. Among 167 eligible patients, 28 experienced composite outcome events over 601.1 person-years. SAPT and DAPT demonstrated clinical benefits over warfarin (SAPT vs. warfarin, adjusted hazard ratio [95% confidence intervals], 0.24 [0.07–0.83]; DAPT vs. warfarin, 0.25 [0.08–0.81]). Notably, DAPT was advantageous regarding major bleeding (DAPT vs. warfarin, 0.10 [0.02–0.47]), while the risk of recurrent thrombotic events was comparable between the antiplatelet and warfarin groups. Antiplatelet therapy may be a safe and effective alternative to warfarin for secondary prevention of aPL- and APS-related stroke. Further prospective validation is required.